THE ROLE OF HEAD TEACHERS IN IMPLEMENTATION OF INCLUSIVE EDUCATION IN PUBLIC PRIMARY SCHOOLS IN KALOLENI - RABAI SUBCOUNTIES, KILIFI COUNTY. - ANDAI, DR. STEPHEN OLUTEYO; MWATELA, MAKONDE WESLEY (IJRDO- Journal of Educational Research, 2017)
Development of inclusive education remains one of the major challenges facing education systems throughout the world. The purpose of this study was to assess the role of head teachers in implementation of inclusive education in public primary schools in Kaloleni - Rabai SubCounties, Kilifi County. The study objectives were to;examine the head teachers’ role of supervision of curriculum in the implementation of inclusive education,assess head teachers’ procurement role in implementation of inclusive education, examine head teachers’ financial management role in the implementation of inclusive education, and to examine the head teachers’ role of teacher management in inclusive education in public primary schools in Kaloleni - Rabai Sub-Counties. It was premised on Systems Approach Theoryand Theories of Inclusive Education. The study adopted a descriptive survey research design. The target population was 18 public primary schools, 18 head teachers and 252 teachers in Kaloleni - Rabai Sub-Counties. A probability sampling techniques using purposive sampling method wasused to select the schools for the study. A sample size of 72 teachers and 18 head teachers were selected yielding to a total of 90 respondents in the study locale. Data was collected using an oral interview for 18 head teachers and a structured questionnairesfor 72 teachers and an observation checklist. The questionnaires were validated through appraisal from the supervisors and education administration experts from the faculty of education and social sciences and then subjected to a pilot study. The reliability of the instruments was tested during the pilot study by testing-retest of the instruments. Descriptive statistics using means mode and frequencieswith some inferential statistics were employed to analyse the data using Statistical Package for Social Science (SPSS) programme version 22. The major study findings revealed that implementation of inclusive education has not been accompanied by effective supervision of the curriculum and procurement of adequate teaching / learning resources from the head teachers in Rabai and Kaloleni Sub- Counties in Kilifi County. The study recommends that head teachers to attain higher qualification to enhance their management capabilities and Ministry of Education to provide capacity building for all head teachers with inclusive education / financial managementskills to enable them effectively undertake their roles of managing schools and to organise for induction programs / workshops / courses for all head teachers and teachers to facilitate them on how to handle SNE learners. The government to employ more SNE teachers, increase more funding to schools to cater for SNE learners and to put in place mechanisms of accountability and quality control of school funds meant for special education. Finally, the study suggested further research on assessment of head teachers’ role in supervision of curriculum in inclusive education, effectiveness of head teachers’ in implementation of inclusive education and a replicate of the same study in other counties in Kenya.